Forensic chemistry - Bell, Suzanne (Harlow, Essex : Pearson, 2014)
The first text to specifically address this growing field, Forensic Chemistry introduces the principal areas of study from the perspective of analytical chemistry--addressing the legal context in which forensic chemistry is conducted, types of samples and matrices, variety of sample types encountered, and extensive use of instrumentation. It provides a solid foundation for basic chemistry, introducing chemical concepts and practices from a forensic perspective (including multivariate statistics, quality assurance/quality control, and protocols used in working forensic laboratories). The Second Edition has been reorganized significantly, and updated to reflect new developments in the course.
Chapter 1- Introduction and Overview- Chemistry and the Law 1.1 What is Forensic Chemistry? 1.2 Precedent in Chemistry and the Law 1.3 Key Forensic and Legal Concepts 1.4 The Flow of a Forensic Analysis 1.5 The Forensic Mind-Set 1.6 Forensic Chemistry Today 1.7 Becoming and Being a Forensic Professional PART 1- METROLOGY Chapter 2- Foundations 2.1 Metrology and Measurement 2.2 Significant Figures, Rounding, and Uncertainty 2.3 Fundamental Statistics 2.4 Error, Accuracy, and Precision 2.5 Hypothesis Testing Chapter 3- Quality Assurance and Quality Control 3.1 Quality Assurance and Quality Control 3.2 Quality Control Procedures 3.3 Quality Control and Calibration Chapter 4- Reporting Defensible Uncertainty and Obtaining Representative Samples 4.1 Uncertainty 4.2 Sampling and Sampling Plans PART 2- CHEMICAL FOUNDATIONS Chapter 5- Chemical Fundamentals: Partitioning, Equilibria, and Acid/ Base Chemistry 5.1 General Considerations 5.2 An Introductory Example 5.3 The Special K's 5.4 Partitioning 5.5 Partitioning with a Solid Phase 5.6 Extension of Partitioning: Thin-Layer Chromatography Chapter 6- Instrumentation 6.1 Microscopes and Chemical Microscopy 6.2 Spectroscopy 6.3 Mass Spectroscopy 6.4 Elemental Analysis 6.5 Microspectrophotometry 6.6 Electrophoretic Instrumentation PART 3- DRUGS AND POISON Chapter 7- Drugs as Physical Evidence: Seized Drugs and Their Analysis 7.1 What is a Drug? 7.2 Classification and Categories 7.3 Drugs as Evidence 7.4 Analysis of Seized Drugs Chapter 8- Forensic Drug Analysis II: Selected Drug Classes 8.1 Acidic and Neutral Drugs 8.2 Basic Drugs Chapter 9- Drugs in the Body 9.1 Introduction 9.2 ADME 9.3 Compartment Models 9.4 Absorption 9.5 Metabolism 9.6 Elimination 9.7 An Integrated Approach 9.8 Dosage Considerations 9.9 How Drugs Work Chapter 10- Forensic Toxicology 10.1 Sample Types 10.2 Categories of Forensic Toxicology 10.3 Analytical Methods PART 4 COMBUSTION EVIDENCE Chapter 11- The Chemistry of Combustion and Arson 11.1 The Combustion Continuum 11.2 Aspects of Combustion 11.3 Flames and Fires 11.4 Arson and Fire Investigation Chapter 12- Explosives 12.1 Explosions, Detonations, and Explosives 12.2 Explosive Power 12.3 Forensic Analysis of Explosives Chapter 13- Firearms and Associated Chemical Evidence 13.1 How Guns Work 13.2 Primers and Propellants 13.3 Forensic Chemical Analysis of Firearms Evidence 13.4 Serial Number Restoration PART 5 MATERIALS Chapter 14- The Chemistry of Colors and Colorants 14.1 Color: A Quantitative View 14.2 Colorants 14.3 Application of Colorants: Inks 14.4 Applications of Colorants: Mechanical and Computer Printing 14.5 Applications of Colorants: Paint Chapter 15- The Chemistry of Polymers 15.1 Polymers 15.2 Biopolymers: Polysaccharides 15.3 Synthetic Polymers Chapter 16- Forensic Analysis of Inks and Paints 16.1 Analytical Methods 16.2 Aging and Dating Appendix 1- Alphabetical Glossary of Terms Appendix 2- Abbreviations Appendix 3- Solvent Properties for SPE and HPLC Appendix 4- Key Organic Chemistry Terms and Reactions Appendix 5- Thermodynamic Quantities Appendix 6- Apothecary and Other Units in Forensic Chemistry Appendix 7- Characteristic Infrared Group Frequencies Appendix 8- Reagents for Color Test Reagents Appendix 9- Tables for Statistical Testing
pharmacy bookfair2016
Includes bibliographical references and index.
Keywords: Chemistry, Forensic; Chemistry, Analytic